The relationship between urogenital fistula and female genital mutilation (Annals of Medical Research, 2021)
Aim: This study investigates the relationship between vesicovaginal fistulas and types of female genital mutilation FGM.
Keywords: Female Genital Mutilation; Urogenital Fistula; Women's Health.